Importance of wheat roots as primary sensors of water deficit - Garcia Girou, N.L.=700 1 Gallez, L.M.; Curveto, N,R.
(Es, En)
ilus., 21 ref.
Keywords: ESTRES; RELACIONES PLANTA AGUA; CRECIMIENTO; RAICES; HOJAS; ESPAÑA; RELACIONES HIDRICAS; DESARROLLO APICAL; RAICES DIVIDIDAS